SYSTEMATIC LITERATURE REVIEW: PROJECT BASED LEARNING MODEL IN JUNIOR HIGH SCHOOL MATHEMATICS EDUCATION - Roiv, Miftahul; Fauziah, Anna; Pandra, Viktor (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
Project Based Learning (PjBL) approach encourages students to be more active, independent, and creative problem solvers, thereby fostering character values such as creativity and curiosity. This research applies the Systematic Literature Review (SLR) method to examine the PjBL model in mathematics education at the junior high school level. PjBL as a learning model involves teachers acting as facilitators who present students with project-based problems to solve independently. This approach stimulates students to design processes and frameworks to find solutions to given problems. The study focuses on various mathematical topics including Flat-Sided Spatial Structures (Cube, Rectangular Prism, and Prism), Curved-Sided Spatial Structures (Sphere, Cylinder, Cone), Quadratic Functions, Trigonometry, and Systems of Linear Equations with Two Variables (SLETV). The analysis concludes that the PjBL model enhances mathematical learning by promoting product-oriented learning, student-centered approaches, fostering critical thinking and real-life problem-solving skills, as well as encouraging collaborative abilities and competition among peers. These findings underscore the effectiveness of integrating PjBL into mathematics education and highlight its implications for fostering holistic student development.